KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SMA NEGERI 1 MEMPAWAH HILIR - F 22211009, Yuliana; Suib, Masluyah; ,, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: As a leader in the school, the principal is responsible for managing all activities of the school, involving teachers who are competent in the field to carry out a given task. The professionalism of the teacher can be seen from the academic qualification data, it showed that the teachers have been through a strata degree, teaching skills and the mastery of the material has shown the quality of the teachers as a professional educators. The strategy to improve the professionalism of teachers leads to quality of teacher training, especially teachers who have been certified. There are some factors that will be faced by the principal such as the lack of facilities, the different perception in every meeting, fund , and the participation of society. Beside that, the principal is also supported by the strategic location of the school, the trust and support from the society about the decision that will be taken, good environment, and the management of schools administration and fund should be transparent and accountable. Keyword: The principal leadership, the professionalsm of the teachers Abstrak: Sebagai pemimpin di sekolah, kepala sekolah bertanggungjawab terhadap semua kegiatan pengelolaan sekolah, melibatkan guru-guru yang kompeten di bidangnya untuk melaksanakan tugas yang diberikan. Gambaran profesionalisme guru jika dilihat dari kualifikasi akademiknya maka diperoleh data bahwa sebagian besar guru telah menempuh jenjang strata satu, kemampuan mengajar serta penguasaan materi sudah menunjukkan kualitas guru sebagai tenaga pendidik yang profesional. Strategi dalam meningkatkan profesionalosme guru mengarah pada pembinaan guru berkualitas terutama guru yang telah bersertifikasi. Faktor penghambat yang dihadapi kepala sekolah berupa keterbatasan fasilitas, menyamakan persepsi pada setiap pertemuan, dukungan dana partisipasi masyarakat, Namun disisi lain kepala sekolah juga didukung oleh letak sekolah yang strategi, kepercayaan dan dukungan masyarakat mengenai berbagai kebijakan yang diambil, lingkungan yang kondusif, serta pengelolaan administrasi dan keuangan sekolah yang transparan dan akuntabel. Kata Kunci: Kepemimpinan Kepala Sekolah, Profesionalisme Guru